Altered Patterns of Amplitude of Low-Frequency Fluctuations and Fractional Amplitude of Low-Frequency Fluctuations Between Amnestic and Vascular Mild Cognitive Impairment: An ALE-Based Comparative Meta-Analysis - Zhang, Xulian; Xue, Chen; Cao, Xuan; Yuan, Qianqian; Qi, Wenzhang; Xu, Wenwen; Zhang, Shaojun; Huang, Qingling (Frontiers in Aging Neuroscience, 2021)
Background: Changes in amplitude of low-frequency fluctuations (ALFF) and fractional amplitude of low-frequency fluctuations (fALFF) have provide stronger evidence for the pathophysiology of cognitive impairment. Whether the altered patterns of ALFF and fALFF differ in amnestic cognitive impairment (aMCI) and vascular mild cognitive impairment (vMCI) is largely unknown. The purpose of this study was to explore the ALFF/fALFF changes in the two diseases, and to further explore whether they contribute to the diagnosis and differentiation of the diseases. Methods: Four meta-analyses were conducted on data from published papers in a systematic review using the method of activation likelihood estimation. Studies were grouped according to outcomes (dementia, cognitive impairment including aMCI, mild cognitive impairment (MCI), and cognitive decline) and output (risk (RR), odd (OR), or hazard ratio (HR)). Results: Compared with healthy controls (HCs), aMCI patients showed increased ALFF/fALFF in the bilateral parahippocampal gyrus/hippocampus (PHG/HG), right amygdala, right cerebellum anterior lobe (CAL), left middle temporal gyrus, (MTG) left cerebrum temporal lobe sub-gyral, left inferior temporal gyrus (ITG) and left cerebrum limbic lobe uncus. Meanwhile, decreased ALFF/fALFF values were revealed in bilateral precuneus (PCUN), bilateral cuneus (CUN), bilateral posterior cingulate (PC) in aMCI patients. Compared with HC, vMCI patients predominantly showed decreased ALFF/fALFF in bilateral CUN, left PCUN, left PC, right cingulate gyrus (CG). Conclusions: The present findings suggested that ALFF and fALFF displayed remarkable altered patterns between aMCI and vMCI when compared with HCs. It may serve as a reliable tool for distinguishing aMCI form vMCI, which may help to understand their pathophysiological mechanisms.